2016
DOI: 10.1080/15384047.2016.1139245
|View full text |Cite
|
Sign up to set email alerts
|

Rapid induction of apoptosis in chronic lymphocytic leukemia cells by the microtubule disrupting agent BNC105

Abstract: Microtubule targeting agents, such as vinblastine, are usually thought to arrest cells in mitosis and subsequently induce apoptosis. However, they can also cause rapid induction of apoptosis in a cell-cycle phase independent manner. BNC105 is a novel vascular and microtubule disrupting drug that also induces apoptosis rapidly but with markedly increased potency compared to vinca alkaloids and combretastatin A4. BNC105 binds to the colchicine-binding site on tubulin resulting in activation of c-Jun N-terminal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…One study in CLL cells demonstrated vinca alkaloid‐mediated apoptosis in 48 h . However, we have recently shown that clinical concentrations of vinca alkaloids or BNC105 can induce CLL apoptosis in only 6 h . As these cells are almost exclusively in G0 this clearly reflects a nonmitotic activity.…”
Section: Consequences Of Microtubule Disruptionmentioning
confidence: 87%
See 2 more Smart Citations
“…One study in CLL cells demonstrated vinca alkaloid‐mediated apoptosis in 48 h . However, we have recently shown that clinical concentrations of vinca alkaloids or BNC105 can induce CLL apoptosis in only 6 h . As these cells are almost exclusively in G0 this clearly reflects a nonmitotic activity.…”
Section: Consequences Of Microtubule Disruptionmentioning
confidence: 87%
“…It is known that JNK can induce Noxa gene transcription, but it is not required in all cell models, suggesting alternative pathways for Noxa upregulation by MDAs. This JNK‐Noxa‐apoptosis pathway is unique to MDAs as taxanes did not yield any of these acute signals in leukaemia .…”
Section: Consequences Of Microtubule Disruptionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Sal-like protein 2 and SP1 share similar DBEs and properties and may cooperatively bind together (56). Furthermore, apoptosis mediated by BNC105, a microtubule-disrupting compound, also led to JNK activation that promoted phosphorylation of ATF2 and induction of ATF3 and Noxa (31). Another study using proteasome inhibitor MG-132 for the induction of apoptosis in MEFs also discovered that JNK1 is needed to trigger cell death and required the presence of c-Myc, but the knockdown did not affect the expression of Noxa (32).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also suggested ATF2, ATF3, and ATF4 as potential transcription factors of Noxa expression (31,32). To understand how Noxa is upregulated after UA treatment, we tested a variety of signaling pathways that may induce Noxa in RASFs, including hypoxia and JNK/ stress-activated protein kinase pathways, as well as pathways that regulate survival, such as Akt and activation of c-Jun.…”
Section: Ua-induced Noxa Upregulation Is Mediated Through Jnk Pathwaymentioning
confidence: 99%